Educational product focusing on sexual education for schoolchildren: Experience report (Research, Society and Development, 2024)
Introduction: Sexuality education is a global concern as it affects everyone's health and well-being. Objectives: To present the structuring of an educational product about children's sexual education, guiding students to recognize their bodies, limits and consent to prevent sexual abuse. Methodology: The development was based on the CTM3 Method: Product design (C); Theoretical Framework (T) and Methodological Framework (M3) based on 3 theories, Transactional Analysis through the Ego States inherent to the human personality, Multisensoriality and Neurolinguistic Programming. The educational product consisted of a roulette wheel with images simulating situations in which children indicate with signs whether they are safe, require attention or are unacceptable. It was used as an anchor using the little monsters of permission. This creation was part of health promotion actions, on the topic of sexual education, where in addition to the educational product created, it addressed body changes, identifying limits, touch through the touch traffic light and educational roulette developed at school linked to the Child Health I module of the Physiotherapy Course. Results and Discussion: During the use of the educational product, a positive impact was noticed, as the students seemed comfortable and interested in the discussion. It was noticed that through the product created it was possible to work on a theme in a respectful and sensitive way. Final Considerations: It is observed that the inclusion of targeted games as an elaborate educational product increases health education actions in general, as it allows knowledge to be realized in a playful and interactive way.